Effect of Ground Force Method on Selected Physical variables among college men kabaddi Players - Vignesh, K.; Ramesh, C (Journal of Neonatal Surgery, 2025)
The purpose of the study was to investigate on Effect of Ground Force Method on chosen Physical variables among college men kabaddi Players. It was hypothesized that here would be significant differences on selected Physical variables due to the effect of Ground Force Method among college men kabaddi players. For the current study the 30 college men kabaddi player from Madurai district. The age of the subjects ranged from 18 to 21 years. The chosen subjects were divided into one experimental group and one control group at random. For the present study pre test and post test random group design, which consists of control group and experimental group was used. On a random sampling, 30 players were selected. The chosen subjects were evenly divided into two group’s of fifteen each namely experimental group with Ground Force Method and Control Group have not underwent any training. Speed was assess by 50mts Dash, Leg Explosive Power was assess by Standing broad jump and Agility was assess by T-Test.The data were collect before and after six weeks of training. The data were analyze by applying t-ratio. The level of significance was set at 0.05 level of confidence. The experimental group show well development on Speed, Leg Explosive Power and Agility among the college men kabaddi players than the control group